PENINGKATAN KETERAMPILAN SOSIAL MEMALUI METODE BERMAIN PERAN DRAMA PADA SISWA KELOMPOK B DI TK AISYIYAH BUSTANUL ATHFAL 58 SURABAYA - abidin, ratno (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
The  problem  in  this  research  is  the  activity  of  learning  in  kindergarten  is monotonous,  as  well  as  filling  the  school  magazine,  drawing  and  coloring  pictures.  In addition, the learning activity is still a lot of emphasis on the academic standing and often using  FAQ  or  lectures  where  teachers  are  more  active  role.  So  the  method  of  playing  the role  is  still  very  rarely  implemented.  Therefore  it  is  necessary  to  do  some  research  related to  the  application  of  methods  play  a  role  to  improve  the  social  skills  of  children .Berdasarkan  results  of  this  study  showed  an  increase  in  social  skills  using  role  play.  Prior to  using  the  method  of  playing  the  role  of  the  social  skills  of  children  lacking  some  social skills, namely a lack of awareness of children to a friend, a lack of respect towards friends, share  the  child's  lack  of  attitude  and  a  lack  of  motivation  to  give  his  friend.  After  going through  the  three  cycles  visible  changes  that  increase  social  skills  children  are  expected  to gradually  increase  the  child  is  more  concerned  about  a  friend,  a  child  can  share  with friends,  children  can  appreciate  and  respect  your  friends  and  children  can  motivate  a friend.  Keywords:  Role Play Methods, Social Skills